SISTEM INFORMASI PELAYANAN PENDAFTARAN PASIEN RAWAT INAP DI PUSKESMAS KUNDURAN KABUPATEN BLORA - Kristiawan Budi Alen; Enny Rachmani; Arif kuriadi (VISIKES: Jurnal Kesehatan Masyarakat, 2013)
Patient data input system at in-patient registration services at local government clinic in kunduran, Blora regency still applicating a manual using register book from in which doctor or specialist’s visit of in-patient record was made then, while patient information data input recoded into patient registrations form and register book, among others are KIUP ( patient main index card ), in-patient register, patient index number book, and in-patient status status card.when patient do not bring any patient main index card (KIUP), they asked to have second checking procedure for their new ones. It is intended to avoid. Therefore, an information system required that can deliver information faster and could make research purpose was to design in-patient registration services information system at local goverment clinic in kunduran, Blora regency. The type of this research is a Research and Development (R and D) where the processes or steps using using were intended to develop a new product or completing existing product. The research data were collected from an observation and interview to the agent of system or agent doer, while the system conducted using SDLC method. Based on the result of in-patient registration services information system research nowdays, it is known that database used in in-patient registration services information system : patient information, terms of payment information, doctor information, registration officer information, and patient room information. Related post involved in in-patient registration services are patient regiatration officer, medical record officer, and head of local government clinic. Information resulted from in-patient information, patient room information, patient of payment information, and patient consultation event information. In-patient regiatration services information system made could help registration and reporting process running easier. To carry out in- patient services, limitation authority access of head of local government clinic, registration officer, medical record officer were occurred. There should be infrastructure and instrument, and also system and hardware maintenance provided in Kunduran local government clinic. Key words : information system, registration in-patient